1995
DOI: 10.1016/0735-1097(95)80011-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of myocardium at risk and collateral flow in acute myocardial infarction using electrocardiographic indexes with comparison to radionuclide and angiographic measures

Abstract: The initial standard 12-lead ECG can provide insight into myocardium at risk and, to a greater extent, collateral flow and can consequently provide some estimate of subsequent infarct size. However, the confidence limits for such predictors are wide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 34 publications
3
44
1
1
Order By: Relevance
“…ST-segment elevation scores correlate closest with both radionuclide and angiographic measurement of collateral flow. 7 The degree of ST elevation is a reflection of the extent of myocardium at risk and is thought to explain the association between the extent of ST elevation during AM1 and a poor outcome. Previous evidence also shows that prolonged ST-segment elevation in the precordial leads during the evolution of anterior…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…ST-segment elevation scores correlate closest with both radionuclide and angiographic measurement of collateral flow. 7 The degree of ST elevation is a reflection of the extent of myocardium at risk and is thought to explain the association between the extent of ST elevation during AM1 and a poor outcome. Previous evidence also shows that prolonged ST-segment elevation in the precordial leads during the evolution of anterior…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…16 However, in patients undergoing reperfusion therapy the correlation between the Aldrich score and the size of the ischemic area at risk (assessed by pretreatment technetium Tc 99 m sestamibi scan or cardiac magnetic resonance imaging) was found to be weak. 17,18 Due to concomitant ischemia of segments that are opposite to each other, occasionally there is cancellation of the ischemic vector and attenuation of ST segment deviation in some segments. It is commonly believed that "anteroseptal" STEMI pattern (ST elevation limited to V 1 -V 3 ) represents a smaller infarct that "extensive anterior" STEMI pattern (ST elevation extension to V 4 -V 6 ) due to an occlusion of a short LAD coronary artery.…”
Section: The Ecg In Patients With Ongoing Typical Symptomsmentioning
confidence: 99%
“…11,12 The use of 99m Tc-sestamibi imaging as a measure of myocardial ischemia severity during coronary occlusion not only in the setting of acute coronary syndrome but also during controlled coronary artery occlusion as in our model, has been validated. 13 Furthermore, we recently demonstrated that the extent and severity of the defect in myocardial perfusion of the territory of the occluded artery are highly correlated with collateral flow reserve, which is a theoretically and clinically well validated index of collateral circulation calculated from coronary pressure during balloon occlusion and can be used for quantitative assessment of collateral blood flow in conscious humans. 14, 15 Pfisterer et al 16 studied 25 patients during elective PTCA of a single LAD lesion and found perfusion defects on occlusion images obtained using 99m Tc-sestamibi.…”
Section: Assessment Of Myocardial Perfusion During Coronary Angioplasmentioning
confidence: 99%